INTERPRETATION OF THE LEGAL FRAMEWORK AND CERTIFICATION PROCEDURES FOR HALAL COMPLIANCE (European Journal of Economics, Finance and Business Development, 2025)
On February 1, 2025, the Cabinet of Ministers of the Republic of Uzbekistan adopted Decision No. 57, establishing the "Regulation on the Procedure for Certifying Products and Services in Compliance with Halal Requirements." This commentary aims to interpret the decree and highlight the importance of the resolution as a significant step in formalizing the process of Halal certification, aligning Uzbekistan’s certification practices with international standards and Islamic principles. The regulation aims to ensure that products and services meet Halal requirements and are suitable for Muslim consumers, creating a legal framework to regulate the certification process and the use of the Halal certification mark.